Pengaruh Pengembangan Karir dan Pelatihan Terhadap Kinerja Personil di Lingkungan Resimen I Pasukan Pelopor Kedung Halang - Jayadi; Adriza; Yuni Pratikno (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to determine the effect of career development and training on personnel performance in the Kedung Halang Police Mobile Brigade Corps Pioneer Regiment I. This study uses a quantitative approach with data collection methods through observation, interviews, and questionnaires distributed to 106 personnel as samples. The data analysis technique used is multiple linear regression to measure the relationship and influence of each independent variable on the dependent variable. The results of the study indicate that, in general, the implementation of the career development programme at the 1st Battalion of the Mobile Brigade Corps is in the moderate category with an average score of 3.29. Career development has a strong relationship with personnel performance, with a correlation coefficient (R) of 0.681 and a determination coefficient (R²) of 0.464, meaning that 46.4% of personnel performance variation is influenced by career development. Furthermore, the implementation of training is rated as good with an average score of 4.08. Training also has a strong relationship with personnel performance, with a correlation coefficient (R) of 0.596 and a coefficient of determination (R²) of 0.355, meaning that 35.5% of performance variation is influenced by training. Overall, personnel performance is in the moderate category with an average score of 3.47. The simultaneous influence of career development and training on personnel performance is indicated by a correlation coefficient (R) of 0.690, showing a strong relationship, and a coefficient of determination (R²) of 0.476, meaning that 47.6% of personnel performance is influenced by both variables together, while the remainder is influenced by other factors.